Phaeoclavulina aurantilaeta (Gomphaceae, Gomphales), a new species of vivid fruiting body from China - Deng, Peng-Tao; Huang, Zhi-Hong; He, Zheng-Mi; Zhang, Ping (Phytotaxa, 2025)
A new ramarioid species, described herein as Phaeoclavulina aurantilaeta, was collected from the Bamian Mountain National Nature Reserve, Hunan Province, China, in 2024. Phylogenetic analyses of the nucleotide sequences of two loci (ITS and LSU) well supported the new species within the genus Phaeoclavulina and formed an independent lineage. This species is characterized by orange with pale red basidiomata, elongate and sub-cylindrical basidiospores with truncate (volcanic) spines. A full description, illustrations, and phylogenetic analysis results of the Phaeoclavulina aurantilaeta sp. nov. are provided. In addition, A key to the known Phaeoclavulina species in China is provided.